2016
DOI: 10.1557/adv.2016.79
|View full text |Cite
|
Sign up to set email alerts
|

Tubulin Nanorings

Abstract: Biological systems routinely produce nanoscopic molecular structures with considerably less dispersion in size and shape than encountered in most manufactured materials. Indeed, Biological structures are frequently and essentially monodisperse. An example of this uniformity, combined with an intriguing geometry, is the nanometer-scale protein nanorings produced by interaction of the protein tubulin with certain hydrophobic tri-, tetra-and pentapeptides originally extracted as natural products from marine biosy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Electron microscopy evidence has shown that plocabulin and its analogous compound PM050489 bind to unpolymerized tubulin and induce the in vitro formation of single-wall tubulin rings composed of 7 ± 1 dimers with average outer diameters of ∼25 nm. Similar single-wall ring assemblies have been found in tubulin complexes with other potent MT-destabilizing agents such as the cryptophycin peptide. On the other hand, rhizoxin binding leads to nonpolymerizable tubulin forms that do not undergo aggregation, whereas vinblastine site ligands promote the assembly of long helical tubulin filaments . Other polymeric structures can also be assembled from tubulin, including large double-wall rings (∼50 nm) from ligand-free tubulin. , Based on this information, it is relevant to evaluate whether MD simulations predict the conformational changes that will lead to oligomeric ring assemblies from plocabulin–tubulin complexes.…”
Section: Results and Discussionmentioning
confidence: 89%
“…Electron microscopy evidence has shown that plocabulin and its analogous compound PM050489 bind to unpolymerized tubulin and induce the in vitro formation of single-wall tubulin rings composed of 7 ± 1 dimers with average outer diameters of ∼25 nm. Similar single-wall ring assemblies have been found in tubulin complexes with other potent MT-destabilizing agents such as the cryptophycin peptide. On the other hand, rhizoxin binding leads to nonpolymerizable tubulin forms that do not undergo aggregation, whereas vinblastine site ligands promote the assembly of long helical tubulin filaments . Other polymeric structures can also be assembled from tubulin, including large double-wall rings (∼50 nm) from ligand-free tubulin. , Based on this information, it is relevant to evaluate whether MD simulations predict the conformational changes that will lead to oligomeric ring assemblies from plocabulin–tubulin complexes.…”
Section: Results and Discussionmentioning
confidence: 89%